The antecedents and outcome of perceived organisational support on turnover intention among direct employees in manufacturing industry - Magespariamal, Chandran (2020)
The purpose of this study was to examine the antecedents and the outcome of perceived organisational support on turnover intention among direct employees in the manufacturing industry. The study also analysed the role of perceived organisational support as a mediator on the relationship. The research framework of this study is developed under the norms of social exchange theory (SET). Questionnaires were distributed to 768 direct employees working in the manufacturing industries in the State of Johor. 437 questionnaires were returned, but only 392 were used in the analysis using the Statistical Package for the Social Sciences (SPSS) method. The data was analyse using various statistical techniques such as correlation, multiple regression and mediation analysis. The results of the study showed a significant and negative effect of perceived co-worker support, distributive justice and procedural justice on turnover intention but perceived supervisor support showed an insignificant effect on turnover intention. The results also revealed a significant and positive effect of perceived supervisor support, coworker support, distributive justice and procedural justice on perceived organisational support. The results also demonstrated the mediating role of perceived organisational support in the link between perceived co-worker support, distributive justice, procedural justice and turnover intention. However, perceived organisational support did not mediate the relationship between perceived supervisor support and turnover intention. The present study also highlighted the implications of the research, future research recommendations as well as its limitations. This study further discusses the theoretical contribution and managerial implications for academics and professionals. The findings in this study can be useful in giving some understandings to the employers, on the effective plans and strategies to deal with the turnover intention wisely.